Modulation of hippocampal dopamine and synapse-related proteins by electroacupuncture improves memory deficit caused by sleep deprivation. Issue 5 (October 2020) - Chen, Danmei; Zhang, Yunpeng; Wang, Cuiting; Wang, Xiaokun; Shi, Jimin; Zhang, Jihong; Guan, Wencai; Li, Bing; Fan, Wei
Background: Sleep is crucial for proper functioning of the brain, whereas lack of sleep is very common in modern society and can cause memory impairment. Hence, it is of great significance to find effective methods to intervene in the pathogenesis of memory impairment. Objective: We designed this study to explore the mechanism underlying the therapeutic effects of electroacupuncture (EA) on the deficits caused by sleep deprivation (SD). Methods: In this study, we first utilized the modified multiple platform method (MMPM) to establish a rat model of SD, which was followed by use of the Y-maze and Morris water maze (MWM) to assess the performance of rats following EA treatment. Results: We found that EA at GV20 and ST36 significantly decreased the number of error reactions, increased the number of active avoidance responses in the Y-maze and shortened the latency of finding the platform in the MWM test in SD + EA versus untreated SD groups. Moreover, EA treatment partially restored SD-induced reductions in hippocampal dopamine (DA) content and significantly increased the levels of phosphorylated (p) synapsin I, calcium/calmodulin-dependent protein kinase (CaMK) II, and tyrosine hydroxylase, which are related to the synthesis and release of DA. Conclusions: In summary, we it appears that EA at GV20 and ST36 may improve SD-induced memory deficits by restoring the quantity of DA in the hippocampus, which is related to activation of CaMK II, synapsin I, and tyrosine hydroxylase. EA may have potential as an alternative therapy for SD and could improve learning and memory deficits among those suffering from sleep deficiency, although this needs verification by prospective clinical studies.